Environmental Health Management and Occupational Health and Safety Practices for Green Hospital Implementation: A Mixed-Methods Study in an Indonesian Public Hospital - Hizriansyah Hizriansyah; Muhammad Nawawi; Hendra Setiawan; Bima Brini Wahyu Setiadi; Arif Andriyanto (Jurnal Ners, 2026)
Green Hospital implementation has become an essential strategy for improving healthcare sustainability by strengthening environmental health management and occupational safety practices. However, empirical evidence regarding EHM and OHS practices supporting Green Hospital implementation in Indonesian public hospitals remains limited. This study aimed to examine EHM and OHS practices supporting Green Hospital implementation at Tripat Gerung Regional Hospital, West Nusa Tenggara, Indonesia. A convergent parallel mixed-methods design was employed. Quantitative data were collected from 68 healthcare workers using a structured questionnaire, while qualitative data were obtained through in-depth interviews with six key informants. Quantitative data were analyzed descriptively, whereas qualitative data were analyzed using thematic analysis and integrated during interpretation. The findings showed that EHM practices were implemented at a fair level (68.9%), with the highest scores observed in medical waste management (79.0%) and environmental sanitation (77.6%), while energy efficiency (57.0%) and resource conservation (58.2%) demonstrated the lowest implementation levels. OHS practices were generally implemented at a good level (71.6%), with hazard identification and risk assessment achieving the highest score (78.4%), whereas regulatory compliance (59.2%) and incident reporting systems (59.6%) remained suboptimal. These findings suggest that successful Green Hospital implementation requires integrated strengthening of environmental health and occupational safety practices, particularly in resource efficiency, governance, and digital reporting systems, to support sustainable healthcare services.